COVID-19: Epidemiological overview of the state of Sergipe (Research, Society and Development, 2023)
Evaluate the prevalence of Covid-19 in the state of Sergipe between the years 2020 to 2023. This is an observational, analytical and ecological study on the prevalence of Covid-19 in the state of Sergipe in the period from 2020 to 2023. data was performed through the website of the Coronavirus Brazil, portal of the Ministry of Health and were stored and processed in spreadsheets and tables in Microsoft Excel format. In the delimited period of the study. Among these cases, the number of 37,449,418 confirmed cases in the country in the year of Covid-19 infection (2020 to date, with the last update of the administrators, dated 04/26) was identified through the Coronavirus Brasil website. /2023 at 11:28). Among these cases, 701,494 are confirmed deaths in the same period. They presented the characterization of the prevalence of Covid-19 in the state of Sergipe between the years 2020 to 2023, and collaborated to understand the chain of factors involved in the rate of accumulated cases. Through the findings found, it is possible to identify an increase in the prevalence of the disease, from 2020 to 2021, with a more abrupt decrease between 2022 and 2023, even the latter not yet finalized. Such values, especially the decrease, is explained by the therapeutic and sanitary conducts developed by the WHO and followed by the Ministry of Health.